"Ministering to the Social Needs of the People": Samuel Jones, Strong Mayor Government, and Municipal Ownership, 1897–1904. (18th January 2016) - Liazos, Ariane
Abstract: Debates in the Progressive era between supporters of the franchise system and supporters of municipal ownership provide an example of conflicting views of appropriate models of state development. The former wanted to continue the public‐private partnerships that characterized much of 19 th ‐century state building, while the latter maintained that this system inevitably led to corruption and exacerbated inequality, calling for a new system of publicly run programs. Mayor Samuel Jones of Toledo worked to expand municipally owned utilities and transportation. Jones argued that granting franchises for the provision of public services enabled private companies to accrue profits that belonged to the people. He actively promoted an alternative model based on his faith in the potential of government, through a program of public ownership, to exemplify a sense of community, brotherhood, and love. Yet obstruction by the city council and lack of mayoral power blocked his efforts. As a result, he attempted to secure a "strong mayor" charter that would enable him to enact his program. The voters, however, rejected the plan, fearing centralization of power and loss of popular accountability. This outcome highlights the importance of the relationship between electoral structures and functional expansion in American political development.